Hemorrhagic syndrome-like disease in calves with bovine viral diarrhea and mucosal disease complex - Dabak, Murat; Karapinar, Tolga; Gulacti, Irem; Bulut, Hakan; Kizil, Omer; Aydin, Suleyman (Wiley, 2007)
Background: Bovine viral diarrhea virus (BVDV) infection is one of the causes of hemorrhagic diathesis in cattle but there have been limited field studies about that condition. Hypothesis: To identify the cause of hemorrhagic diathesis in calves and describe its clinical findings. Animals: Five calves from a farm with 150 dairy cows. Methods: Clinical examination of the calves was performed. After blood samples were obtained from 2 calves, whole blood, sera, and leukocyte samples were used for hematologic and hemostatic examinations, neutralization tests, virus isolation, and viral genome sequencing. Results: The calves had moderate pyrexia, dullness, serous or mucous nasal discharge, and petechial and ecchymotic hemorrhages on mucosal surfaces. Severe thrombocytopenia and anemia were identified on hematologic examinations. All calves died within 10 days of the onset of clinical signs. Virologic examinations identified BVDV as the causative agent of the disease. Conclusions and Clinical Importance: This paper identifies a hemorrhagic syndrome-like disease in calves with bovine viral diarrhea and mucosal disease complex in Turkey.
Keywords: cattle; hemorrhagic dysfunction; pestivirus; thrombocytopenia